NANOSTRUCTURAL PROCESSES OF MELTING AND MOULDING OF CAST IRON WITH GLOBULAR GRAPHITE - E. I. Marukovich; V. Yu. Stetsenko (Литьë и металлургия)
It is shown that melting and molding of cast iron with globular graphite are complex physical and chemical nanostructural processes. The major role in these processes is played by the centers of crystallization of dendrites of graphite, graphite nanocrystals, the dissolved and adsorbed oxygen. The role of the modifying ligature of FeSiMg is reduced generally to essential decrease of concentration of the adsorbed oxygen and an enrichment of fusion by the centers of crystallization of graphite dendrites.